Screening and classification of genotypes for seedling-stage chilling stress tolerance in rice and validation of the trait using SSR markers. Issue 3 (14th July 2015) - Pradhan, S. K.; Nayak, D. K.; Guru, M.; Pandit, E.; Das, Sujata; Barik, S. R.; Mohanty, S. P.; Anandan, A.
Abstract : Low-temperature stress is an important factor affecting the growth and development of rice in temperate and high-elevation areas. In this study, 220 germplasm lines were used for screening of tolerant genotypes, validation of molecular markers and identification of robust markers for seedling-stage chilling stress tolerance to be used in marker-assisted breeding (MAS) programme. The temperature regimes imposed in the growth chamber simulated cold-stress injuries at the seedling stages of the germplasm lines. The genotypes were classified into six classes: those having susceptible genotypes were classified into moderately and highly susceptible types, while tolerant types into moderately tolerant, tolerant, highly tolerant and very highly tolerant classes. Genotypes namely Langma, Umleng-1 and Geetanjali showed survival up to 25 d, which were better than the positive check Kalinga-III surviving up to 20 d under chilling stress. Ten simple sequence repeat (SSR) markers were tested for differentiation of genotypes. Individual use of SSR markers like RM284, RM286, RM85, RM341 and RM5746 can be applied in MAS breeding including combination use of non-pair markers like RM284, RM239 and RM85, which was even better than the combined use of RM284 and RM85. However, combined use of all ten markers can most effectively be employed for cold tolerance through MAS breeding.